Predicting limiting 'free sugar' consumption using an integrated model of health behavior. (1st July 2020) - Phipps, Daniel J.; Hagger, Martin S.; Hamilton, Kyra
Abstract: Excess intake of 'free sugars' is a key predictor of chronic disease, obesity, and dental ill health. Given the importance of determining modifiable predictors of free sugar-related dietary behaviors, we applied the integrated behavior change model to predict free sugar limiting behaviors. The model includes constructs representing 'reasoned' or deliberative processes that lead to action (e.g., social cognition constructs, intentions), and constructs representing 'non-conscious' or implicit processes (e.g., implicit attitudes, behavioral automaticity) as predictors of behavior. Undergraduate students ( N  = 205) completed measures of autonomous and controlled motivation, the theory of planned behavior (TPB) measures of explicit attitude, subjective norms, perceived behavioral control (PBC), and intentions, past behavior, implicit attitude, and behavioral automaticity at an initial point in time, and free sugar limiting behavior and behavioral automaticity two weeks later. A Bayesian structural equation model indicated that explicit attitude, subjective norms, and PBC predicted behavior via intention. Autonomous motivation predicted behavior indirectly through all TPB variables, while controlled motivation predicted behavior only via subjective norms. Implicit attitudes and behavioral automaticity predicted behavior directly and independently. Past behavior predicted behavior directly and indirectly through behavioral automaticity and intentions, but not implicit attitudes. Current findings suggest pervasive effects of constructs representing both reasoned and non-conscious processes and signpost potential targets for behavioral interventions aimed at minimizing free sugar consumption.